Pengaruh Kualitas Produk Murabahah, Harga, Dan Kualitas Pelayanan Terhadap Kepuasan Nasabah Di Baitul Maal Wat Tamwil Nurul Ummah Ngasem Bojonegoro - Moch Zaenal Azis Muctharom; Moh. Agus Sifa' (JOURNAL OF SHARIA ECONOMICS, 2019)
Abstract This study aims to clearly describe the quality of murabahah, haraga, service quality and customer satisfaction at Baitul Maal Wat Tamwil Nurul Ummah Ngasem-Bojonegoro. The second objective is to examine the significant influence of murabaha product quality on customer satisfaction. The third objective is to examine the significant effect of Price on customer satisfaction. The fourth objective is to examine the influence (quality of murabaha products, Price and Service Quality) silmutanously on customer satisfaction. The fifth objective is to test the most dominant (murabaha product quality, price and service quality to customer satisfaction). The study population is the Customer at Baitul Maal Wat Tamwil Nurul Ummah Ngasem-Bojonegoro. Sampling amounted to 56 respondents. Analysis of the study was conducted using data collection methods, questionnaires, interviews, observation and documentation. Data analysis techniques using SPSS 19.0 with the stages are (1) validity and reliability test (2) multiple regression analysis (3) hypothesis testing is t test and f test. Descriptive analysis results show: The results of the study indicate that there is a significant influence between product quality on customer satisfaction, while price has no significant effect on customer satisfaction and service quality has no significant effect on customer satisfaction. Between product quality, price and quality services, the most dominant influence on customer satisfaction in KJKS BMT Nurul Ummah Ngasem-Bojonegoro is product quality. Keywords: Murabaha product quality, price, service quality and customer satisfaction